1H NMR and HPLC-DAD-MS for the characterization of ellagitannins and triterpenoids of less investigated Anogeissus leiocarpus DC (Combretaceae) stem bark. (1st May 2022) - Akande, Titilayo; Khatib, Mohamad; Ola Salawu, Sule; Afolabi Akindahunsi, Akintunde; Di Cesare Mannelli, Lorenzo; Ghelardini, Carla; Balli, Diletta; Cecchi, Lorenzo; Mulinacci, Nadia
Highlights: Hot water extraction allowed maximizing the total tannin recovery from AL stem bark. 43 ellagitannins and 16 triterpenoids have been identified in stem bark extracts. Vescalin, castalin and roburin were detected for the first time in Anogeissus l . HPLC-DAD-MS analysis allowed identifying 5 olean-type triterpenoid derivatives. Aqueous extracts exerted protection against osteoarticular pain in rats. Abstract: Anogeissus leiocarpus DC is an evergreen tree, widely distributed in Asia and Africa. The stem bark is used in traditional medicine, and as chewing sticks and infusion. Nowadays, it is becoming increasingly important to define the phytochemical profile of less studied edible plants. Aim of this research was a first complete characterization of ellagitannins and triterpenoids profiles by HPLC-DAD-MS and 1 H NMR and analyses. A total of 59 compounds were identified including 43 ellagitannins and 16 triterpenoids, mainly oleane derivatives and glycosylated forms. Among ellagitannins, roburin, vescalin and castalin were found for the first time. Tannins accounted for 38.9% whereas triterpenoids were 4.8%, both estimated on dry decoction. The decoction was preliminary tested against osteoarthritis in rats. The characterization of the main phytochemicals of Anogeissus leiocarpus DC stem bark decoction is a necessary step to evaluate nutraceutical properties, paving the way for possible food applications of this plant.